Contextual Teaching and Learning for Teacher Professionalism in Inclusive Early Childhood Education - Junarti, Junarti; Rauf, Isfaur (Journal of Innovation and Research in Primary Education, 2025)
Inclusive early childhood education requires teachers to possess professional competencies in managing diverse learner needs, yet many kindergarten teachers lack adequate training in implementing effective inclusive pedagogies. This study investigated the implementation of Contextual Teaching and Learning (CTL) to enhance teacher professionalism in managing inclusive classrooms at Darul Falah Islamic Kindergarten, East Kutai Regency, Indonesia. Employing a School Action Research design across two cycles with four instructional sessions, the study involved two kindergarten teachers and utilized structured observation instruments validated by expert reviewers. Data were analyzed using both quantitative methods (percentage calculations with predetermined success criteria) and qualitative approaches (thematic analysis following Miles and Huberman's framework). Results demonstrated substantial improvements in teacher implementation proficiency, increasing from 66.66% in Cycle I Meeting 1 to 86.66% in Cycle II Meeting 2, while student engagement levels improved from 53.33% to 83.33% across the same period. Both metrics exceeded the 80% success threshold by the intervention's conclusion. The iterative cycles of planning, implementation, observation, and reflection enabled teachers to progressively develop competencies in connecting curriculum content with students' lived experiences, facilitating collaborative learning communities, and employing authentic assessment strategies. These findings provide empirical evidence supporting CTL as an effective approach for enhancing teacher professionalism in inclusive kindergarten contexts, with significant implications for teacher education programs and professional development policies.